Crecimiento económico y su relación con la asignación de recursos financieros por departamentos periodo 2017 – 2022 - Panduro Reategui, Diana Miluska (2025)
Weak economic growth and the projected slowdown increase inequalities, affecting urban and rural areas due to the lack of economic diversification and the concentration of resources in central areas due to the inequity in budget allocation across regions. Therefore, this research determines the relationship between economic growth and the allocation of financial resources by department during the 2017-2022 period, considering a quantitative, observational approach and a correlational-causal non-experimental design. The study population consists of data on economic growth and the allocation of financial resources corresponding to the departments of Peru. The work concludes that economic growth increased on the coast, with a total that went from S/359,513 million in 2017 to S/403,068 million in 2022, with Lima standing out as the main contributor, accounting for 62% of regional growth. In the highlands, economic growth showed a moderate increase, rising from S/84.558 billion to S/87.059 billion, with stable financial allocations at relatively moderate amounts, with departments such as Cusco and Cajamarca standing out, despite the fact that economic growth in this region presented significant deviations from normal. In the jungle, growth increased from S/23.687 billion to S/25.263 billion, and the allocation of financial resources showed variations, with Loreto and San Martín being the main recipients. On the other hand, correlation analyses indicated that there is no statistically significant relationship between economic growth and the allocation of financial resources in the coast (p=0.846), highlands (p=0.872), or jungle (p=0.457) regions.